Advanced aqueous rechargeable lithium battery using nanoparticulate LiTi(2)(PO(4))(3)/C as a superior anode - Sun, Dan (Sci Rep, 2015)
Poor cycling performance arising from the instability of anode is still a main challenge for aqueous rechargeable lithium batteries (ARLB). In the present work, a high performance LiTi(2)(PO(4))(3)/C composite has been achieved by a novel and facile preparation method associated with an in-situ carbon coating approach. The LiTi(2)(PO(4))(3)/C nanoparticles show high purity and the carbon layer is very uniform. When used as an anode material, the ARLB of LiTi(2)(PO(4))(3)/C//LiMn(2)O(4) delivered superior cycling stability with a capacity retention of 90% after 300 cycles at 30 mA g(−1) and 84% at 150 mA g(−1) over 1300 cycles. It also demonstrated excellent rate capability with reversible discharge capacities of 115 and 89 mAh g(−1) (based on the mass of anode) at 15 and 1500 mA g(−1), respectively. The superior electrochemical properties should be mainly ascribed to the high performance of LiTi(2)(PO(4))(3)/C anode, benefiting from its nanostructure, high-quality carbon coating, appropriate crystal structure and excellent electrode surface stability as verified by Raman spectra, electrochemical impedance spectroscopy (EIS), X-ray diffraction (XRD) and scanning electron microscopy (SEM) measurements.